Análisis de la influencia de factores geotécnicos de suelos en la susceptibilidad a deslizamientos - Tejada Beltrán, Fabio Andrés (Escuela Colombiana de Ingeniería Julio Garavito, 2020)
In many of the investigations where an evaluation of threat and susceptibility of movements to mass movements is carried out, geotechnical factors are not directly included in determining the influence that these parameters have on the occurrence of the event; This leads to deficiencies in the characterization of the elements that affect it, and that in one way or another can contribute to the development or proliferation of this type of natural phenomena, typical of steep slopes. The inclusion of these aspects was then sought, making a compilation of the history of cases of landslides that were documented, identifying geotechnical parameters that could have contributed to their development; finding typical values in different ranges, which allowed to compare real conditions of events studied in different places, managing to analyze the way in which these elements contribute to the event. This exercise contributed to the proposal of a methodology that contributes to the interpretation of the level of susceptibility of some types of materials in the occurrence of mass movements, facilitating the characterization of risk areas that violate the integrity of the infrastructure and the population.
Keywords: Deslizamiento; Suelos residuales; Geotecnia; Glide; Residual soils; Geotechnics